Essentials of accounting for governmental and not-for-profit organizations - Copley, Paul A. (McGraw-Hill, 2007)
Copley and Engstrom’s Essentials of Accounting for Governmental and Not-for-Profit Organizations, 8e is best suited for those professors whose objective is to provide more concise coverage than is available in larger texts as well as for those professors whose objective is to prepare accounting majors for the uniform CPA Examination in the areas of state and local governmental accounting, accounting for not-for-profit organizations, governmental auditing, and taxation of exempt entities.